Ways to improve interactivity of Internet GIS - Paliulionis, Viktoras (Lietuvos matematikos rinkinys, 2021)
The essential feature of Internet GIS is the interactivity between the users and the spatial data. Interactive GIS can offer interactive maps rather than static map images on the Web. Users can work with the maps interactively by performing conventionalGIS functions such as zoom, pan, search, etc. However, the interactivity of many InternetGIS is quite limited so far. In this paper, we propose to use AJAX to improve the interactivity of Internet GIS. AJAX design patterns that can be used to this aim are described in the paper. We present the architecture of the Internet GIS with AJAX-based user interface and integration with GIS web services.
Keywords: GIS; Internet GIS; Ajax; GIS architecture